The Effect of Competence, Integrity, And Work Motivation Of The Treasurer Of Expenditure On Good Governance Of State Financial Management (Study On The Financial Affairs Of The Work Unit Within The Police Headquarters) - Patria Priambudi; Rien Agustin Fadjarenie (Cita Konsultindo Research Center, 2023)
This research is the first or new research conducted at the National Police Headquarters, so the variables used are also new variables related to the public sector government so that it can provide input to the world of academia that it is necessary to build a theory regarding the public sector government. One of the antecedents or indicators are competence and integrity. The purpose of this study was to analyze the influence of the competence, integrity, and work motivation of treasurers on the good governance of state financial management in the financial affairs of work units within the Police Headquarters. This type of research is quantitative, and the population in this study is financial affairs in work units within the National Police Headquarters, totaling 65 work units. The sampling technique used in this study used a whole-sample sampling from members of the population, called the census technique or saturated sampling. so that the number of samples used in this study were all members of the population, namely 65 Expenditure Treasurers. The data collection technique used in this study was to use questionnaires and interviews with 10 Expenditure Treasurers as respondents in order to strengthen the results of the research. The data analysis technique uses the SmartPLS 3.0 program. The results of the study show that the competency and integrity of the Spending Treasurer have a positive and significant effect on good governance of state financial management. Meanwhile, the work motivation of the Expenditure Treasurer has no significant effect on the good governance of state financial management.